2012
DOI: 10.1007/s10006-012-0368-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between head injury and facial trauma: a case–control study

Abstract: Present study revealed that fracture of facial bones, especially bones that are in anatomic proximity to the cranium and need a high magnitude of trauma energy to be fractured, was marker for an increased risk of head injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
69
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 25 publications
8
69
7
Order By: Relevance
“…Mainly documented etiologic factor for injury was RTA with 69.38%, followed by assault (16.76%), fall (11.04%) and sports injury was (2.87%). As shown in With respect to associated injuries, a sum of 48 patients introduced head injuries and other concomitant injuries as described in Figure- 17 and study conducted by Grant Al clearly indicated Incidence of brain injury was 67% overall which is not similar with results of our study. 18 It is hard to separate the mortality & dreadfulness of maxillofacial fractures associated with it.…”
Section: Resultscontrasting
confidence: 78%
“…Mainly documented etiologic factor for injury was RTA with 69.38%, followed by assault (16.76%), fall (11.04%) and sports injury was (2.87%). As shown in With respect to associated injuries, a sum of 48 patients introduced head injuries and other concomitant injuries as described in Figure- 17 and study conducted by Grant Al clearly indicated Incidence of brain injury was 67% overall which is not similar with results of our study. 18 It is hard to separate the mortality & dreadfulness of maxillofacial fractures associated with it.…”
Section: Resultscontrasting
confidence: 78%
“…It is also not clear how the diagnosis of facial injuries was made or confirmed (facial x-rays of CT scan). Although in conclusion, it has been suggested that "the patients with concomitant head and facial injuries had a high GCS score (12-15) at the time of admission" [1] However, it has not been well supported by the results of the study.…”
mentioning
confidence: 70%
“…
Dear Sir, We read the article "The relationship between head injury and facial trauma: a case-control study" [1] with great interest. In the present prospective study, the authors discuss their experience with the pattern of facial bone fractures and their correlation with intracranial injuries.
…”
mentioning
confidence: 99%
See 2 more Smart Citations